Assessment of Knowledge Levels Following an Education Program for Parents of Children With Inflammatory Bowel Disease - Vernon-Roberts, Angharad; Gearry, Richard B.; Day, Andrew S. (Frontiers in Pediatrics, 2020)
Children with inflammatory bowel disease (IBD) and their parents have increasing roles in disease management and require sufficient, appropriate information for communication with their clinical team. Formal education is effective at improving disease knowledge, disease outcomes and mental health, yet few interventions have been targeted for parents of children with IBD. A two day parent education program was held at the annual residential camp for children with IBD in New Zealand with knowledge levels tested pre and post intervention using a validated assessment tool: IBD-KID2. Thirty parents consented, 70% female and 83% had a child with Crohn’s disease. The pre-intervention mean score (maximum fifteen) was 10.6 (SD 2.9), with no associations with independent variables. Knowledge levels increased significantly following the education program to a mean 12.6 (SD 2.0) (p <0.005). Disease specific knowledge may improve outcomes and should, therefore, be reinforced during clinic encounters and regarded as an ongoing endeavor.